Wireless Power Charging in Electrical Vehicles - Nassim Iqteit, Khalid Yahya, Sajjad Ahmad Khan (IntechOpen, 2021)
Wireless Power Transfer (WPT) technology can transfer electrical energy from a transmitter to a receiver wirelessly. Due to its many advantages, WPT technology is a more adequate and suitable solution for many industrial applications compared to the power transfer by wires. Using WPT technology will reduce the annoyance of wires, improve the power transfer mechanisms. Recently, the WPT gain enormous attention to charging the on-board batteries of the Electric Vehicle (EV). Several well-known car manufacturing companies start efforts to adopt WPT technology and enhance its features. Therefore, WPT can be achieved through the affordable inductive coupling between two coils named a transmitter and a receiver coil. In EV charging applications, transmitter coils are located underneath the road, and receiver coils are installed in the EV. The inductive WPT of resonant type is generally applied to medium-high power transfer applications like EV charging because it achieves better energy efficiency. In this chapter, various WPT technologies are discussed and tested in EV wireless charging applications. Furthermore, extensive information is given to developing an advanced WPT technology that can transfer maximum power by achieving maximum efficiency.